Enzymatic Characterization of Recombinant Cyclodextrin Glycosyltransferase from Bacillus sp. a2-5a using Sagoo Starch as Substrate - RINA IMANIAR; CATUR RIANI; DESSY NATALIA; DEBBIE SOFFIE RETNONINGRUM (Microbiology Indonesia, 2012)
Cyclodextrin (CD) is a cyclic oligosaccharide molecule and depending on the number of glucose molecules, three types of CDs are commonly used, α-CD, β-CD, and γ-CD. CDs can be produced enzymatically using starch as substrate catalyzed by CD glycosyltransferase (CGTase). In current research, recombinant CGTase production from the synthetic gene was optimized for its production using three growth media and two induction temperatures. The highest yield was obtained in Luria Bertani medium at 25 °C. The rCGTase protein was affinity purified as a 76.39 kDa protein which showed α-cyclization and starch hydrolysis activities using zymography method. The optimum temperature, pH and incubation time was 55 °C, 6, and 24 h, respectively. The enzyme was stable at a wide pHs in the range of 5-10, retained its half activity at 56 °C for 30 min and had cyclization ratio for α-CD : β-CD : γ-CD was 4 : 81 : 15. An amount of 542 mg β-cyclodextrin was produced from 100 mL reaction of 1% (b/v) sagoo starch using 38.4 μg rCGTase in optimum condition. This work reports for the first time the character of rCGTase from Bacillus sp. A2-5a using sagoo starch as a substrate.